Evaluating the Role of the Multidisciplinary Team from the Perspective of Teachers in Learning Disabilities Programs Attached to Primary Schools - Al-Gabbani, Sarah AbdelRahman; Al-Abdul-Jabbar, AbdulAziz Mohammed (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to assess the role of the multidisciplinary team, identify its challenges, and explore strategies to overcome them from the perspective of female teachers working in learning disabilities programs attached to primary schools in Riyadh. The study adopted a descriptive survey approach, and a randomly selected sample of 214 female teachers of students with learning disabilities participated. A questionnaire was used as the primary data collection tool. The findings revealed that the overall mean score for evaluating the role of the multidisciplinary team was (3.02), indicating a moderate level. The perceived challenges scored an overall mean of (3.29), also reflecting a moderate degree. The most significant barriers included the team’s reliance on the learning disabilities teacher and the general education teacher in managing cases, as well as the dependence on a single member to carry out the team’s responsibilities. The study proposed several strategies to enhance the effectiveness of multidisciplinary teams, most notably: emphasizing the importance of their role in the official procedural and organizational guidelines of special education, and assigning a coordinator responsible for organizing team meetings and facilitating collaboration among team members.